90 Implantable cardiac defibrillator deactivation; contemporary outcomes from a large case series. (17th July 2020) - Garner, Daniel; Blackburn, Matthew; Llewellyn, Jennifer; Rao, Archana; Hughes, Sue; Wright, David
Abstract : Introduction: Implantable cardiac defibrillator (ICD) therapy is a lifesaving intervention for many of our patients, however with increasing age and competing comorbidity towards the end of life device therapy is often no longer advantageous. Historically advance care planning and discussions around deactivation of ICD's have been lacking(1) and this has resulted in a large number of patients receiving inappropriate ICD shocks at the end of life.(2) We conducted a retrospective analysis of all patients under-going device deactivation to identify trends in outcomes and rates of inappropriate shock. Methods: Our electronic patient record was searched for all ICD deactivations between 2016 and 2019. These results were incorporated with hospital episode statistics to gather mortality and morbidity data. Results: During the study period 327 patients had device deactivation performed and 293 unfortunately died. The cohort was predominantly male (84%) and the ICD had been implanted for on average 5.1 years, with devices predominantly implanted for primary prevention (64%). Devices were most commonly deactivated in the inpatient hospital setting (45%), with 15% turned off in clinic and 11% in the patients home. 71% of deactivations occurred prior to death with palliative/end of life care being the most common indication. 29% had devices deactivated after death and this caused 11 (3.8%) patients to have one or multiple shocks at the time of death (range 1-18, mean 4.5). 5.1% of patients received shocks in the last month of life. Conclusions: A significant proportion of ICDs are still deactivated after death. The number of patients experiencing shocks at the end of life was lower than previously published literature but this is still a source of significant avoidable morbidity. ICD deactivation should be discussed with patients prior to implant and services need to be able to regularly review the ongoing appropriateness of device therapy. Conflict of Interest: None